Ammonia-oxidizing bacteria rather than archaea respond to short-term urea amendment in an alpine grassland. (April 2017) - Xiang, Xingjia; He, Dan; He, Jin-Sheng; Myrold, David D.; Chu, Haiyan
Abstract: Chemical fertilizers, especially nitrogen (N) and phosphorus (P), are used in grasslands to maximize plant biomass production for livestock. Despite a substantial body of work on how fertilization affects aboveground plant and belowground microbial communities, the short-term response of soil ammonia-oxidizing microbial communities, which play the central role in nitrification, to fertilization is not well understood. The responses of ammonia-oxidizing microbial communities to short-term (3 years) N and/or P additions were investigated in an alpine grassland of the Qinghai-Tibetan Plateau. Quantitative polymerase chain reaction (qPCR) analysis of the amoA genes showed that ammonia-oxidizing archaea (AOA) dominated over ammonia-oxidizing bacteria (AOB) in non-amended soil. Short-term urea addition significantly increased the abundance of AOB, whereas AOA abundance remained unchanged, resulting in a shift from AOA to AOB dominance, which suggests that AOB are likely to be more important in the first step of the nitrification following urea amendment. Pyrosequencing demonstrated a significant shift in AOB but not AOA community composition within short-term N fertilizer plots, indicating that AOB community composition was more sensitive than AOA in response to urea amendment. This study demonstrated that the abundance and composition of AOA and AOB communities responded differently to 3 years of urea addition, suggesting that N fertilizer may be an important controller of ammonia-oxidizing microbial communities in managed alpine grasslands, such as those of the Qinghai-Tibet Plateau. Graphical abstract: Highlights: Addition of N + P significantly increased aboveground biomass and decreased plant diversity. Addition of N or N + P triggered the shift from AOA to AOB dominance. Community composition of AOB, but not AOA, was significantly altered by N amendment. Addition of P had little effect on ammonia-oxidizing microbial communities.